Anestezjologia i Intensywna Terapia Ropivacaine and bupivacaine in combined epidural and general anaesthesia for pulmonary resection - Misiołek, Hanna; Werner, Małgorzata; Kucia, Hanna; Karpe, Jacek; Budziński, Dariusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Background: Thoracotomy for pulmonary resection is accompanied by stress response related to pain. The current gold standard of anaesthesia for thoracic surgery including epidural analgesia combined with general anaesthesia attenuates the negative effects of stress by sympathetic suppression. Bupivacaine used for epidural analgesia is frequently replaced by a new local anaesthetic – ropivacaine. Reduced cardio- and neurotoxicity are important advantages of ropivacaine. Aim: We compared 0.75% ropivacaine and 0.5% bupivacaine used epidurally in combination with general anaesthesia on haemodynamic and ventilatory parameters during thoracotomy with one lung ventilation. Material and methods: 63 patients undergoing pulmonary resection were scheduled in the study. In group I (n=32) bupivacaine epidural analgesia was used and in group II (n=31) analgesia was maintained with ropivacaine. Heart rate, systolic, diastolic and mean blood pressure, arterial oxyhaemoglobin saturation (SpO2), end-tidal carbon dioxide (ET CO2) and hourly diuresis were monitored during the procedure. Results: 3 patients, who did not meet the inclusion criteria, were excluded from the study. In group I, significant decrease of systolic blood pressure after a dose of bupivacaine for induction of anaesthesia as well as lowest SpO2 were observed during the operation. After 30 min. of one lung ventilation increased ET CO2 was noticed in both groups. Despite equal amount of infused liquids, hourly diuresis was increased in the ropivacaine group. Conclusions: Ropivacaine epidural analgesia combined with general anaesthesia for pulmonary resection provides better haemodynamic stability and ventilatory parameters in comparison to combined general and epidural anaesthesia with bupivacaine. We propose that ropivacaine may be more valuable in a group of patients ventilated with selective one lung ventilation technique.